Phenological aspects and variation of chlorophylls a and b contents in caryocar-brasiliense camb - Soavs, RDF; Dasilva, O. A. (Inst Tecnologia Parana, 1993)
There were detected variations of chlorophylls a and b during the senescence leaves period of Caryocar brasiliense Camb in the Corumbatai cerrado vegetation, State of São Paulo. The highest peak of total chlorophylls a and b contents was registered after the maximum leaves expansion, while the lowest peak it was obtained at leaves abcision. The chlorophylls a and b variations can be explained as a function of a chlorophyll a variation content. The phenological events studied (flowering and fruiting time, leaf fall and sprouting) showed a marked periodicity during the year. Flowering and fruiting time have a similar peak both in the wet season (september to february). Leaves fall occurred in the dry season with the peak in August.
Keywords: CHLOROPHYLLS; PHENOLOGY; CARYOCAR; CERRADO VEGETATION; INTRODUCAO